2009
DOI: 10.1177/229255030901700401
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Outcomes Between Immediate and Delayed Repair of Mandibular Fractures

Abstract: Medical records of patients treated with surgical repair of mandible fractures by the otolaryngology and plastic surgery departments at a level 1 trauma centre were obtained and reviewed. Two study groups were compared: patients treated within 72 h of the injury and those treated after this time period. Patient demographics, time to repair, fracture types, substance abuse history, etiology, surgical management, complications and length of hospital stay were assessed. The complication rate was 41% (n=7) within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
1
14
1
Order By: Relevance
“…Conversely, Biller et al [ 1 ] reported that complications increased with treatment delay. The present study differed from these previous reports [ 1 , 6 ] as substance abuse was cited in both as a risk factor in the development of complications, and the method of treatment was by rigid internal fixation, while the role of posttraumatic pain and trismus were not assessed. However, Hermund et al [ 5 ] and Hurrell and Batstone [ 13 ] reviewed the literature and stated that with the current research evidence based on treatment outcome a definitive conclusion cannot be drawn on the optimal timing of the treatment of mandibular and other facial fractures.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Conversely, Biller et al [ 1 ] reported that complications increased with treatment delay. The present study differed from these previous reports [ 1 , 6 ] as substance abuse was cited in both as a risk factor in the development of complications, and the method of treatment was by rigid internal fixation, while the role of posttraumatic pain and trismus were not assessed. However, Hermund et al [ 5 ] and Hurrell and Batstone [ 13 ] reviewed the literature and stated that with the current research evidence based on treatment outcome a definitive conclusion cannot be drawn on the optimal timing of the treatment of mandibular and other facial fractures.…”
Section: Discussioncontrasting
confidence: 89%
“…These variables were the direct and immediate consequence of the inflammatory response associated with the traumatic injuries that led to the fractures [ 3 , 4 ]. Webb et al [ 6 ] observed that complication rates were lower when repair of mandibular fractures was delayed beyond 72 h, and suggested that a delay in treatment was more cost-effective than early (immediate) treatment. Conversely, Biller et al [ 1 ] reported that complications increased with treatment delay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown no increase in complications with a delay of repair beyond 24 hours until 7 days. 23,24 In our sample, stabilization was performed with 3D rhombic condylar fracture plate .This type of osteosynthesis showed none of the plates fractured, none bent or loosened screws during all recall periods, this is due to its rhombus shape which provides internal stability, as well as more optimal leverage that counteract posterior or anterior loads onto the proximal fragment.…”
Section: Discussionmentioning
confidence: 85%